INNOVATIVE MECHANICS OF ACTIVITIES IN THE DIGITAL ECONOMY IN SAMARKAND CITY HOTEL ENTERPRISES (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Today, the rapid development of the tourism sector in Uzbekistan is associated with their transfer to the digital economy. In Uzbekistan, the digital economy is relatively well structured in hotels within the network and industry enterprises. If so, the transfer of all low-power hotels to the ham digital economy is relevant.